Problem from Bonevac’s Book

José Guilherme

New member
Joined
Feb 14, 2019
Messages
4
Problem from Bonevac’s Book

So there is this sequent from Bonevac’s book “Deduction” that I’m not quite seeing how to solve it. Looking at the exercise it appears to be obvious but I’m not being able to finish the formal demonstration.
The exercise is the following:

Vx (3yFxy -> VyFyx); 3x3yFxy; therefore VxVyFxy

Any comment would be most welcomed.

(I'm using "V" as the universal quantifier and "3" as the existential quantifier.)
 

ksdhart2

Full Member
Joined
Mar 25, 2016
Messages
984
So what we have here is:

\(\displaystyle \forall x (\exists y F_{xy} \implies \forall y F_{yx})\)

\(\displaystyle \exists x \exists y F_{xy} \therefore \forall x \forall y F_{xy}\)

Is that correct?
 

José Guilherme

New member
Joined
Feb 14, 2019
Messages
4
So what we have here is:

\(\displaystyle \forall x (\exists y F_{xy} \implies \forall y F_{yx})\)

\(\displaystyle \exists x \exists y F_{xy} \therefore \forall x \forall y F_{xy}\)

Is that correct?

Yes.
The first two propositions are the premisses and the third the conclusion that we have to show.
 
Top